Evaluation of 2-Thioxoimadazolidin-4-one Derivatives as Potent Anti-Cancer Agents through Apoptosis Induction and Antioxidant Activation: In Vitro and In Vivo Approaches - Mohamed S. Nafie; Ahmed I. Khodair; Hebat Allah Y. Hassan; Noha M. Abd El-Fadeal; Hanin A. Bogari; Sameh S. Elhady; Safwat A. Ahmed (Molecules, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the most widespread malignancies and is reported as the fourth most prevalent cause of cancer deaths worldwide. Therefore, we aimed to investigate the probable mechanistic cytotoxic effect of the promising 2-thioxoimidazolidin-4-one derivative on liver cancer cells using in vitro and in vivo approaches. The compounds were tested for the in vitro cytotoxic activity using MTT assay, and the promising compound was tested in colony forming unit assay, flow cytometric analysis, RT-PCR, Western blotting, in vivo using SEC-carcinoma and in silico to highlight the virtual mechanism of action. Both compounds 4 and 2 performed cytotoxic effects against HepG2 cells with IC50 values of 0.017 and 0.18 μM, respectively, compared to Staurosporine and 5-Fu as reference drugs with IC50 values of 5.07 and 5.18 µM, respectively. Compound 4 treatment revealed apoptosis induction by 19.35-fold (11.42% compared to 0.59% in control), arresting the cell cycle at G2/M phase. Moreover, studying gene expression that plays critical roles in cell cycle and apoptosis by RT-PCR demonstrated that compound 4 enhances the expression of the pro-apoptotic genes p53, PUMA, and Caspase 3, 8, and 9, and impedes the anti-apoptotic Bcl-2 gene in the HepG2 cells. It can also inhibit the PI3K/AKT pathway at both gene and protein levels, which was reinforced by the in silico predictions of the molecular docking simulations towards the PI3K/AKT proteins. Finally, in vivo study verified that compound 4 has a promising anti-cancer activity through activating antioxidant levels (CAT, SOD and GSH) and ameliorating hematological, biochemical, and histopathological findings.